The Economic Purposes Related to the Labor Types - Lee, Sih; Kim, Sangyong; Lee, Yang (Archives of Business Research, 2019)
What are purposed by economic activities are contained in types of labor and are related with varieties of personal livings. The economic purposes cover over supporting life, pursuing wealth, and developing society and culture, each of which constrains the related economic ideologies as liberalism, socialism, and information society. The labor types are differentiated as physical, emotional, and cognitional. This study attempted to analyze the three economic purposes which are hypothesized to be varied due to the three labor types. The experiment illustrated the three models in their job activities, each of whom was engaged in one of the three economic purposes, which is related with one of the three labor types, and questioned with Likard scales about how high the models engaged in the labor types and worked for the economic purposes. The experimental result showed that the supporting life is comprised by the physical labor, the pursuing wealth by the emotional labor, and the developing society and culture by the cognitional labor. So, it is suggested that the relation of labor types and economic purposes should be conferred to go ahead to a solution for economic-social problems imbed in ideologies.